KONSISTENSI PEMBENTUKAN PERATURAN DAERAH BERDASARKAN HIERARKI PERUNDANG-UNDANGAN DALAM PERSPEKTIF HUKUM KEPEGAWAIAN - S.Sos, SH.MH, adrie; Suardita, I Ketut (Fakultas Hukum Universitas Ngurah Rai, 2024)
Governmental authority is more or less left to regional governments as is the case with laws and regulations through the establishment of regional regulations (Perda) which must also meet conditions such as consistency in the formulation of standard structure and language, and the existence of a harmonized relationship between various laws and regulations. The purpose of this scientific work is to find out the process of forming regional regulations from the perspective of personnel law and to find out the consistency of the formation of regional regulations based on the hierarchy of legislation from the perspective of personnel law. The writing of this paper uses the normative legal research method using library research by inventorying and quoting legal science literature books, statutory provisions as well as scientific essays and lecture notes that are related to writing this scientific work. The conclusions from writing this scientific paper include (1) the process of forming regional regulations (Perda) from the perspective of personnel law consists of three stages, namely (a) the process of preparing the draft Perda which is the process of drafting and designing within the DPRD or within the Regional Government, consisting of preparation of academic texts and draft regional regulations; (b) the process of obtaining approval, which is discussed in the DPRD; (c) the process of approval by the Regent and promulgation by the Regional Secretary; (2) the consistency of the formation of regional regulations (Perda) based on the hierarchy of legislation in the perspective of personnel law with legal commitments that must be enforced so that the Regional Regulations (Perda) made do not violate the hierarchy and violate the constitution and for Civil Servants who do not comply with the provisions can be subject to prosecution Discipline Punishment according to Government Regulation Number 94 of 2021 concerning Employee Discipline.